All that Curves is Not Effusion - Suhas H. S; Ketaki Utpat; Unnati Desai; Jyotsna M. Joshi (Journal of Krishna Institute of Medical Sciences University, 2017)
Endobronchial tuberculosis is a peculiar variant of tuberculosis hallmarked by involvement of the tracheobronchial tree and contributes to a sizable proportion to the overall morbidity due to the disease. Bronchostenotic variety is the predominant pattern with clinical spectrum ranging from asymptomatic affection to significant life threatening luminal compromise. The radiological features could be deceptive leading to a diagnostic delay. Awareness of the spectrum of the clinical manifestations and heterogeneity in radiological patterns is therefore vital for an accurate diagnosis. We hereby narrate a case of bronchostenotic variant of endobronchial tuberculosis overtly seeming like a pleural effusion on the basis of a chest radiograph.